Co-Expression of LGR5 and CD133 Cancer Stem Cell Predicts a Poor Prognosis in Patients With Gastric Cancer - Wareeporn Wattanawongdon; Wareeporn Wattanawongdon; Theeraya Simawaranon Bathpho; Theeraya Simawaranon Bathpho; Taweesak Tongtawee; Taweesak Tongtawee (Turkish Journal of Gastroenterology, 2021)
Background: The LGR5 and CD133 have been identified as cancer stem cells (CSCs) marker and prognostic marker in several cancers including gastric cancer. The purpose of the present study was to determine the association between co-expression of CSCs marker LGR5 and CD133 in patients with gastric cancer and their clinicopathological outcomes; to analyze the efficacy of co-expression of both markers in evaluating the prognosis of gastric cancer. Methods: LGR5 and CD133 expression were investigated in a total of 400 patients by using immunohistochemistry. Results were analyzed in association with patient characteristics outcomes. Overall survival was performed using Kaplan-Meier Curve analysis. Results: LGR5 and CD133 were found positive in 219/400 (54.75%) and 251/400 (62.75%) respectively in gastric cancer tissues. Co-expression of LGR5 and CD 133 were significantly associated with poor clinicopathological outcomes, including lymphatic invasion, vascular invasion, higher pathological T stage, and higher TNM staging (stage IV) (P < .05). The overall survival of patients who were positive for LGR5 and CD133 had shorter than that of LGR5 and CD133-negative gastric cancer, especially in patients who were positive for both markers. Conclusion: Our finding indicates that co-expression of LGR5 and CD133 could be used as a marker indicating poor prognosis, which can provide information for selected effective treatment and carried out of intensive follow-up in gastric cancer patients. Cite this article as: Wattanawongdon W, Bathpho Simawaranon T, Tongtawee T. Co-expression of LGR5 and CD133 cancer stem cell predicts a poor prognosis in patients with gastric cancer. Turk J Gastroenterol. 2021; 32(3): 261-268.